Management of disappearing colorectal liver metastases: an international survey. Issue 4 (April 2021) - Melstrom, Laleh G.; Warner, Susanne G.; Wong, Paul; Sun, Virginia; Raoof, Mustafa; Singh, Gagandeep; Chavin, Kenneth D.; Fong, Yuman; Adam, Rene; Hugh, Thomas J.
Abstract: Background: Improved chemotherapy response rates have lead to "disappearing" colorectal liver metastases (dCRLM). We aim to assess management patterns of dCRLM from an international body of hepatobiliary surgeons. Methods: A survey was designed, tested for item relevance, readability and content validity, and distributed to the AHPBA, IHPBA and ANZHPBA. Results: The majority of 226 respondents were <15 years from training (69%), practiced in academia (82%) and devoted >50% of their practice to hepatobiliary (75%). Surgeons utilize CT(45%) or MRI(47%) for preoperative planning with a preferred imaging interval of <6 weeks. Nearly all have experienced dCRLM (99%) and 63% of surgeons have waited a few months to assess for durability of response prior to definitive surgical/ablative therapy. Only 24% place fiducial markers for lesions <1-cm prior to neoadjuvant chemotherapy. Intra-operatively, 97% of surgeons perform ultrasound, and 71% ablation. When a tumor has "disappeared, " 49% elect for observation and 31% resect if the dCRLM is superficial. Of those electing observation, 87% believe there is effective treatment with progression on surveillance imaging. Conclusions: Nearly all surgeons have experienced dCRLM with half choosing observation over intervention due to the belief that these lesions may be re-addressed in the future.